Factors Influencing the Adoption of Artificial Intelligence Technologies by Academic Library Staff: An Applied Study on the Central Library at the University of Benghazi Using the TAM Model. (Comprehensive Journal of Science, 2026)
This study aimed to identify the factors influencing the adoption of artificial intelligence (AI) technologies by staff in academic libraries, focusing on the Central Library of the University of Benghazi. The study utilized the Technology Acceptance Model (TAM) as a theoretical framework to understand the behaviors of library staff towards AI technologies. A quantitative approach was employed, with a structured questionnaire consisting of three sections: demographic information, variables related to AI adoption, and challenges and needs associated with the implementation of these technologies.The sample for the study consisted of 30 library staff members from various academic and professional backgrounds at the Central Library of the University of Benghazi. The findings revealed that the primary factors influencing AI adoption were perceived usefulness and perceived ease of use, both of which had a positive impact on the staff's intention to adopt these technologies. Additionally, organizational, personal, and psychological factors related to staff awareness and understanding of AI's potential to enhance library services were identified, The study recommends enhancing training strategies and technical capacity-building for library staff, along with fostering a supportive environment for technological change to ensure the successful integration of AI in academic libraries with limited resources.